Win Son presents a Taiwanese American cookbook - Ku, Josh; Brown, Trigg; Erway, Cathy (Abrams, 2022)
"A modern, brashly flavorful guide to cooking Taiwanese-American food, from Brooklyn's lauded Win Son, Win Son Bakery, and Cathy Erway, celebrated writer and expert on the cuisine. Josh Ku, born in Queens to parents from southern Taiwan, and Trigg Brown, a native Virginian whose mentor was a Taiwanese-American chef, forged a friendship over food--specifically, excellent tsang ying tou, or "flies' head," a dish of chopped budding chives kissed with pork fat. Their obsession with Taiwanese food and culture propelled them to open Win Son together in 2016. The East Williamsburg restaurant quickly established itself as a destination and often incurs long waits for their vibrant and flavorful Taiwanese-American cuisine. Ku and Brown have teamed up with Cathy Erway, Taiwanese food expert and celebrated writer, to create this book which explores and celebrates the cuisine of Taiwan and its ever-simmering pot of creative influences. Told through the eyes, taste buds, travels, and busy lives of Ku, Brown, and Erway, this book brings the cuisine of this misunderstood island nation into the spotlight. With 100 creative, yet accessible recipes, this book will unravel the history of this diaspora cuisine. While featuring classic dishes and well-known favorites, this cookbook also stretches this cuisine's definition, introducing new dishes with brazen twists that are fun, flavorful, and decidedly American-born in style"--Amazon.